RARE-29. AZD8055 ENHANCES IN VIVO EFFICACY OF AFATINIB IN CHORDOMAS. (11th November 2019) - Zhao, Tianna; Siu, I-Mei; Williamson, Tara; Zhang, Haoyu; Ji, Chenchen; Burger, Peter; Cottone, Lucia; Flanagan, Adrienne; Hann, Christine; Gallia, Gary
Abstract: INTRODUCTION: Chordomas are rare, locally aggressive bone tumors that arise in cranial base, mobile spine, and sacrum. Currently, there are no FDA-approved therapies for chordoma patients, thus there is a high unmet need to develop effective treatments. In this study, we aim to evaluate the anti-tumor efficacy of small molecule inhibitors that target crucial oncogenic pathways in chordoma, as single agents or in combination, to identify novel therapies with the greatest translation potential. METHODS: A panel of small molecule compounds that had exhibited in vitro efficacy against human chordoma cell lines or target known chordoma drivers was screened in vivo against patient-derived xenograft (PDX) models of chordoma, and their efficacy was further evaluated using chordoma cell lines and xenograft models. RESULTS: The in vivo activity of compounds identified in a NIH Chemical Genomics Center screen utilizing chordoma cell lines, together with inhibitors of c-MET and PDGFR, were evaluated in PDX models of chordoma that were previously described or recently established for this study. Inhibitors of EGFR (BIBX1382, erlotinib and afatinib), c-MET (crizotinib) or mTOR (AZD8055) significantly inhibited tumor growth in vivo but did not induce tumor regression. Co-inhibition of EGFR and c-MET using erlotinib and crizotinib synergistically reduced cell viability in chordoma cell lines but did not result in enhanced in vivo activity. Co-inhibition of EGFR and mTOR pathways using afatinib and AZD8055 synergistically reduced cell viability in chordoma cell lines. Importantly, co-inhibition of EGFR and mTOR also synergistically suppressed tumor growth in vivo, showing improved disease control. CONCLUSION: Single inhibition of EGFR, c-MET or mTOR suppresses chordoma growth both in vitro and in vivo . Co-inhibition of EGFR and mTOR synergistically inhibits chordoma growth in a range of preclinical models. The insights gained from our study provide a novel combination therapeutic strategy for patients with chordoma.